MANAJEMEN PENJAMINAN MUTU INTERNAL - Fatkhur Rohman; Nurhayati Nurhayati; Toni Julham (Jurnal Sabilarrasyad, 2020)
Quality management is a set of procedures and processes to improve performance and improve work quality. The essence of quality management is a management system that is continuously endeavored and directed to increase customer satisfaction at a low cost. Cost reduction is due to the quality of the product and is free from failures resulting in losses so that the ratio between output and input is very high. The development of Quality Assurance in Education, the objectives of guarantee (Assurance) for the quality are as follows. 1) Assist continuous and continuous improvement and improvement through best practices and willingness to innovate, 2) Make it easy to get help, either money loans or facilities or other assistance from strong institutions that can be trusted. 3) Providing information to the community according to the target and time consistently, 4) Ensuring that there are no unwanted things.